2020
DOI: 10.35912/joste.v1i3.367
|View full text |Cite
|
Sign up to set email alerts
|

Customer behavior impact on international tourist's travel intention due to Covid-19

Abstract: Purpose: Several industries affected by the Covid-19 outbreak – one of the most affected is the tourism industry due to travel restrictions, which have resulted in an unprecedented slump in the number of international tourists. This situation has an impact on changing consumer behavior towards intention to travel. This study aims to measure the impact of Covid-19 on international tourists' consumer behavior towards crises to intention to travel overseas after the pandemic is over. Research methodology: A pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…Similarly, prior research has supported that hygiene, health preventive behavior, familiarity with COVID-19, have a positive impact on tourist travel behavior (Chua et al, 2020;Gupta et al, 2021;Riestyaningrum et al, 2020). A recent study found that tourist decisions to visit during the COVID-19 Pandemic were positively affected by health awareness (Zainuddin et al, 2022).…”
Section: 223mentioning
confidence: 85%
See 1 more Smart Citation
“…Similarly, prior research has supported that hygiene, health preventive behavior, familiarity with COVID-19, have a positive impact on tourist travel behavior (Chua et al, 2020;Gupta et al, 2021;Riestyaningrum et al, 2020). A recent study found that tourist decisions to visit during the COVID-19 Pandemic were positively affected by health awareness (Zainuddin et al, 2022).…”
Section: 223mentioning
confidence: 85%
“…We found that most of the empirical research was carried out in Indonesia (n 5 12) (Afriani and Sugiarto, 2020;Alwi et al, 2022;Azis et al, 2020;Bustan and Setiawan, 2021;Kadir et al, 2020;Lemy et al, 2020;Pinem et al, 2021;Sianipar et al, 2021;Sihotang and Sukaatmadja, 2021;Sitinjak et al, 2021;Sukaatmadja et al, 2022;Zainuddin et al, 2022). After that, 7 studies were based on the data collected from China (Agyeiwaah et al, 2021;Cai et al, 2021a;Han et al, 2021;Hu and Xu, 2021;Jiang et al, 2022;Riestyaningrum et al, 2020;Zeng and Li, 2021) followed by the Malaysia (n 5 5) (Ahmad et al, 2021a, b;Hanafiah et al, 2021;Ramli et al, 2021;Tiam Chin et al, 2021) and India (n 5 4) (Gupta et al, 2021;Kour et al, 2021;Rather, 2021a, b) and in Korea (n 5 4) (Shin et al, 2022;Sinha and Nair, 2021;Yoo et al, 2022;Yu et al, 2021). We also noted that three studies were conducted in the USA context (Chua et al, 2020(Chua et al, , 2021Milman et al, 2020;Rasoolimanesh et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“… Luo and Lam (2020) found that fear of COVID-19 directly affects travel anxiety and risk attitude, which have direct negative effects on travel intention. Riestyaningrum et al (2020) found that the pandemic had significant partial effects on international tourists’ travel intentions. Zenker et al (2021) tested how tourists’ travel intentions are affected by their intra-personal anxiety.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The risks associated with human activities even affect people's willingness to travel [36]. For example, volcanoes, tsunamis, earthquakes, and typhoons, among the natural disasters that may occur in tourist destinations [37][38][39][40][41], and crime risk, political risk, and terrorism risk, among the man-made tourism risks, can all affect tourists' scheduled travel plans [42][43][44][45][46][47]. During the COVID-19 period, most of these risks have not been applicable, and people have mainly considered the health risks.…”
Section: Risk Perception 221 Travel Risksmentioning
confidence: 99%